1987
DOI: 10.1159/000199508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bisacodyl on Intestinal Electrolyte and Water Net Transport and Transit

Abstract: The effect of bisacodyl on intestinal electrolyte, glucose, and water transport, and transit was studied in 6 healthy volunteers by intestinal perfusion. A 5-lumen tube with an occluding balloon allowed constant perfusion (10 ml/min) of 30 cm of the upper jejunum and a rapid collection of the perfusate free of contaminants. A phenol red bolus was injected into the tube and its passage through the test segment was calculated by dye dilution formula. A 1-hour control period was followed by a test period with 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
2
16
0
2
Order By: Relevance
“…It is difficult to imagine how this mode of action can cause the rather fast onset response in our tissue preparations. Our findings agree with an earlier study performing bisacodyl perfusion in colonic and jejunal loops in healthy volunteers . The authors found an increased K + secretion.…”
Section: Discussionsupporting
confidence: 93%
“…It is difficult to imagine how this mode of action can cause the rather fast onset response in our tissue preparations. Our findings agree with an earlier study performing bisacodyl perfusion in colonic and jejunal loops in healthy volunteers . The authors found an increased K + secretion.…”
Section: Discussionsupporting
confidence: 93%
“…About 50% of the dose is eliminated in the faeces as BHPM (14). Bisacodyl has been used in the past for similar sampling procedures (15), and its effects on the intralumenal physiology have been shown to be reversible (16,17). Table I shows the exact colon preparation procedures applied in the pilot study, together with food consumption details prior to each colonoscopy.…”
Section: Pilot Studymentioning
confidence: 99%
“…Both these diphenyl methane derivatives are prodrugs converted in the gut into the same active metabolite, bis-(p -hydroxyphenyl)-pyridyl-2-methane (BHPM). BHPM has a dual action, namely an antiabsorptive-secretory effect and also a direct prokinetic effect [5] [6]. Only minor amounts are systemically absorbed but are not considered to contribute to the laxative action since the laxative effect of bisacodyl or SPS does not correlate with the plasma level of BHPM.…”
Section: Introductionmentioning
confidence: 99%